Mediastinal parathyroidectomy by VATS for persistent, sporadic primary hyperparathyroidism in an adolescent - Lynda Ngo; Chris Wang; Alicia C. Greene; Anthony Y. Tsai; Afif N. Kulaylat; Brian D. Saunders (Elsevier, 2023)
Primary hyperparathyroidism (PHPT) is an endocrine disorder that is commonly diagnosed in adults. PHPT is less commonly seen in the pediatric age range, and when identified, non-syndromic disease is unusual. PHPT caused by an ectopic parathyroid gland is rare, especially in the adolescent population, and may contribute to disease persistence. Because parathyroidectomy is the only known curative treatment for PHPT, localization of the abnormal gland(s) preoperatively is often attempted, and is critical prior to re-operation. Recurrent or persistent PHPT continues to be a surgical challenge because parathyroidectomy via traditional cervical incision may not be feasible for parathyroid adenomas located in an ectopic location. When identified in the thymus, minimally invasive approaches are preferred over sternotomy or thoracotomy because of decreased morbidity rates and improved patient outcomes. Recently, parathyroidectomy via video-assisted thoracoscopic surgery (VATS) for mediastinal parathyroid adenomas has been described in the literature. We report a case of a non-syndromic adolescent with persistent PHPT who was cured after undergoing mediastinal parathyroidectomy via VATS approach while utilizing intraoperative parathyroid hormone guidance and frozen-section pathologic analysis.